Perception of undergraduate nursing students regarding e-learning during COVID-19 pandemic in West Bengal - Sasmal, Suvashri; Roy, Moitreyee (International Journal Of Community Medicine And Public Health, 2021)
Background: The education system has faced severe trouble worldwide in COVID-19 pandemic since the beginning of 2020. In this context every educational institute including nursing colleges has adopted E-learning for smooth continuation of teaching learning process. Keeping this in mind this descriptive survey study aimed to identify the perception of the undergraduate nursing students towards E-learning during COVID 19 phase. Methods: A cross sectional web-based survey has been conducted through Google form with in west Bengal. By using snowball sampling, 327 sample were selected as study participants and they were received the structured questionnaire and submitted after giving their responses. Data were extracted and analysed with the help of different descriptive statistics, such as frequency, percentage, mean, median, standard deviation and inferential statistics in terms of chi-square by using SPSS 20.0 (IBM SPSS Statistics for Windows, version 20.0). Results: In this article 327 participants were enrolled among them 70.95% had indifferent perception, whereas only 14.07% possessed unfavourable perception towards E-learning. Compared with the indifferent percentage the participants with favourable perception was very less i.e. only 14.98%. We also found perception of E learning has no association with demographic variables but significant association is there between gadgets used to attend E learning. Conclusions: Nursing faculties need to address the student’s perception towards e-learning so that efforts can be directed towards improving their learning experience.